Pemodelan Matematika Terhadap Keuntungan Harian Pada Penjualan Jajanan Dikafe Nihayah Pondok Putri Pesantren Zainul Hasan - Djeni, Darwin; Zamania, Tutus; Siti Nor Hasanah, Indah (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2021)
ABSTRACT This study aims to analyze the daily profit associated with the sale of snacks at the Nihayah cafe, Pondok Putri, Pesantren Zainul Hasan. The mathematical model in this study uses Multiple Linear Regression. The analysis in this study used the SPSS 20 program application. The results of this study were a mathematical model of multiple linear regression, namely. Y = -0.360 + 0.215X_1 + 0.122X_2 + 0.088X_4 + 0.109X_5 + 0.107X_6. With the largest profit coefficient on Monday, which is equal to 0.215.